Quality of Life of Thyroid Cancer Patients with Radioactive Iodine Ablation and Its Predictors: A Hospital Based Survey - Hossain, AKM Farhad; Khatun, Sayada Fatea (Bangladesh Armed Forces Medical Journal, 2026)
Background: Despite high survival rates, treatment and disease-related factors can significantly impact the quality of life (QoL) in thyroid cancer patients, underscoring the importance of identifying key predictors for targeted supportive care. This study aims to assess QoL and its predictors in thyroid cancer patients following thyroidectomy and radioactive iodine (RAI) ablation. Methods: A cross-sectional analytical study was conducted between August 2022 and July 2025 among purposively selected 218 thyroid cancer patients post-thyroidectomy followed by radioactive iodine therapy at a specialized hospital, Dhaka. Data were collected through face-to-face interviews using a validated, pretested, semi-structured questionnaire and checklist. Written informed consent was obtained, and all ethical principles were strictly followed. Results: The study reveals a female predominance (64.2%), with a mean age of 44.14 ± 15.41 years, and nearly half of participants being under 40. Most had SSC-level education (37.6%), were married (72.9%), and belonged to lower-income groups (74.3%), with a significant portion being housewives (34.9%). The study highlights the average QoL was 89±13. Significant predictors of QoL included age, education, marital status, and income. Older age and being married were linked to lower odds of good QoL (OR=0.100, p<0.05), while higher education (OR=1507.114) and income (OR=0.027) were associated with higher QoL scores (p<0.05). Age, education, and income significantly influence different domains of QoL after RAI ablation. Conclusion: Thyroid cancer patients report better quality of life across various domains after radioactive iodine therapy.The findings highlight that addressing age-related challenges and improving education and social support can significantly enhance quality of life in thyroid cancer patients after RAI therapy. These insights can inform strategies to policymakers, healthcare providers, and researchers in improving quality of life for diverse patient groups, with future research on RAI’s long-term impact and personalized survivor care. Bangladesh Armed Forces Med J Vol 58 No (2) December 2025, pp 1-10